9.7%-efficient Sb2(S, Se)3 solar cells with a dithieno[3, 2-b: 2′, 3′-d]pyrrole-cored hole transporting material. Issue 1 (21st December 2020) - Jiang, Chenhui; Zhou, Jie; Tang, Rongfeng; Lian, Weitao; Wang, Xiaomin; Lei, Xunyong; Zeng, Hualing; Zhu, Changfei; Tang, Weihua; Chen, Tao
Abstract : An efficient device based on the Sb2 (S, Se)3 /DTPTHMe-ThTPA heterojunction offers an effective approach to engineer the interfacial carrier transport path for high power conversion efficiency. Abstract : Antimony selenosulfide, Sb2 (S, Se)3, is a promising next-generation solar cell material with superior photovoltaic properties and high stability. However, the efficiency of Sb2 (S, Se)3 solar cells lags far behind its theoretical value and other well-established thin-film solar cells. Herein, we report a one-step hydrothermal process by employing selenourea as a selenium source for a single-phase and compact Sb2 (S, Se)3 light absorber film, which possessed a desirable bandgap of 1.50 eV. When a low-cost and planar dithieno[3, 2- b :2′, 3′- d ]pyrrole-cored small molecule (DTPThMe-ThTPA) is used as the hole transporting material, the interfacial energy level alignment is optimized. We disclose that chemical interaction formed between neighbouring thiophene and Sb atoms is critical for carrier collection and suppression of charge recombination, resulting in a champion efficiency of 9.7% with DTPThMe-ThTPA and increased stability, which is comparable to the device based on conventional Spiro-OMeTAD.